دور الدبلوماسية الثقافية العمانية في تعزيز الهوية العربية الإسلامية. = The role of Omani cultural diplomacy in promoting Arab-Islamic identity. - Ahmad al-Habsi, Salim Hilal Ahmed; U Tun Aung, Maulana Akbar Shah (القرارة ـ غرداية ـ اجلزائر, 2021)
تعتبر سلطنة عمان من الدول الأوائل التي إستخدمت الدبلوماسية الثقافية في علاقاتها الدولية. فقد جعلها العمانيون من نمط حياتهم، وسلوكيات تعاملهم مع الشعوب الأخرى. فموقع سلطنة عمان المطل على سواحل المحيط الهندي من نافذة بحر العرب جعل من العمانيين بالإشتغال في التجارة البحرية مع الصين ودول شرق آسيا وصولا إلى جنوب شرق إفريقيا. ونظرا لامتلاك العمانيين حضارة تاريخية في هذه المناطق وتأثيرهم وتأثرهم بها ساعدهم في نشر الإسلام وقيمهم وعاداتهم وتقاليدهم العمانية والعربية فيها. وفي هذا البحث تم التطرق إلى تاريخ وأهمية الدبلوماسية الثقافية العمانية وأهم المشاريع الثقافية النوعية التي قامت بها سلطنة عمان لتعزيز الهوية العربية والإسلامية كمشروع بيت الإسلام (القرية العمانية) في هولندا، ومشروع معرض رسالة الإسلام من عمان، ومشروع إعلان السلطان قابوس للمؤتلف الإنساني، لتبقى خالده في أذهان الشعوب. ************************************************************************** The Sultanate of Oman has been one of the first countries to deploy cultural diplomacy in its international relations. Omanis have made it part of their lifestyle, and their behaviour with other peoples. Overlooking the Indian Ocean from the Arabian Sea, the country’s location leads its people to engage in maritime trade with China and East Asian countries, reaching Southeast Africa. As Omanis had a historical civilization in these areas, where they both had influence and were subject to the influence, they were able to spread Islam, their values, customs and Omani and Arab traditions there. In this research, the history and importance of Omani cultural diplomacy and the most important cultural projects undertaken by the Sultanate of Oman to promote Arab and Islamic identity, such as the House of Islam project (the Omani Village) in the Netherlands, Oman's Message of Islam exhibition, and the Sultan Qaboos Declaration Project on United Human Values, to perpetuate them in peoples’ minds.